INTELLECTUAL TRADITION AMONG ULAMA: STUDY OF IBN MALIK’S ALFIYAH BOOK - Nata, Abuddin; Sanusi, Jafar; Sofyan, Ahmad (FIKRAH, 2022)
The development of science, culture and Islamic civilization, among others, is marked by the presence of a number of great scholars whose works can still be found easily to this day. In addition to writing various kinds of Islamic religious knowledge, such as interpretation, hadith and fiqh, the scholars also wrote books that discussed Arabic grammar and literature, namely nahwu, sharaf, balaghah, bayan, ma’ani and bade’ sciences. Among the books that discuss the science of Arabic grammar is Ibn Malik’s Alfiyah. This book is very popular among scholars and students at Islamic boarding schools in Indonesia in particular and in the world in general. Besides being read and understood, this book is also generally recited before the fardlu prayer, and memorized. One of the reasons is because everyone who wants to study religion is required to master grammar with its various branches as a tool to understand various Arabic literature, hereinafter referred to as the Yellow Book (because the paper is yellow), or the Gundul Book (because the writing does not use signs). read). By using authoritative library data, this paper will further explore the intellectual tradition practiced by Ibn Malik through his work Alfiyah. This paper begins by presenting a brief biography of the author of the Alfiyah book, its contents, the intellectual tradition that he adheres to, as well as the winged meaning of several stanzas contained in the book.